2018
DOI: 10.1002/pssr.201800100
|View full text |Cite
|
Sign up to set email alerts
|

Rare‐Earth Ion Local Environments in Nd:Al2O3‐P2O5‐K2O Glass Studied by Electron Paramagnetic Resonance Spectroscopies

Abstract: The rare-earth local environments of Nd:Al 2 O 3 -P 2 O 5 -K 2 O glass with different P/Al ratios are analyzed using electron paramagnetic resonance (EPR). The echo-detected field sweep (EDFS) line-shape change hints at a modification of the local environment around Nd 3þ ion by various P/Al ratios. The coordination sphere structure of Nd 3þ ion is determined by three and four pulse electron spin echo envelope modulation (ESEEM) spectra. The off-diagonal signal corresponding to 31 P Larmor frequency confirms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In the recent years, the composition of the nearest neighbors shell around a rare-earth ion in RE doped silica fibers (and also in other glasses 19 ) has been investigated 2022 . Still little is known concerning the formation of the nearest neighbors shell around a RE ion.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, the composition of the nearest neighbors shell around a rare-earth ion in RE doped silica fibers (and also in other glasses 19 ) has been investigated 2022 . Still little is known concerning the formation of the nearest neighbors shell around a RE ion.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the optical properties of Nd 3+ ions are highly dependent on the glass structure and their local ligand environment . Glass structure is hard to be comprehensively characterized due to the disorder arrangement of atoms and the low resolution of traditional techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Schneider et al 8 suggested that six-fold coordinated aluminum (Al Ⅵ ) restricted the migration of phosphate chains resulting in an enhancement of T g in (1−x)NaPO 3 It is known that the optical properties of Nd 3+ ions are highly dependent on the glass structure and their local ligand environment. [11][12][13][14] Glass structure is hard to be comprehensively characterized due to the disorder arrangement of atoms and the low resolution of traditional techniques. The solid-state nuclear magnetic resonance (SSNMR) technique is a powerful tool to characterize the hyperfine structure of glass materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photodetectors are an indispensable core component in many modern precision analytical, measurement and diagnostic instruments . Photodetectors fabricated using heterojunctions are superior to those fabricated with homojunctions in the aspect of low dark noise, etc . Graphene is a hexagonal 2D film composed of a single layer of sp 2 hybrid carbon atoms, which has the potential ability of fast photoresponse .…”
Section: Comparison Of Response Time (Rise Time) Of Our Device and Otmentioning
confidence: 99%